A brief web‐based screening plus emotional‐disorder health education was associated with improvement of mental health awareness and service‐seeking attitudes among patients seeking nonpsychiatric clinical services in China. Issue 5 (22nd November 2020) - Kang, Yukun; Wang, Huiyao; Li, Xiaojing; Tao, Yujie; Yang, Xia; Deng, Wei; Yu, Jianying; Zhou, Qian; Li, Tao; Guo, Wanjun
Abstract: Objectives: Low recognition and intervention rates of emotional disorders among nonpsychiatric clinical patients are primarily attributable to poor mental health awareness of patients and a paucity of mental health care resources. This study aims to investigate the association of a resource‐saving brief web‐based emotional‐disorder self‐screening plus a health self‐education program (BWBED‐SS + HSE) with improved mental health awareness and service‐seeking attitudes among nonpsychiatric clinical patients. Method: A sample of 2065 patients seeking health services in nonpsychiatric clinical settings underwent BWBED‐SS + HSE using mobile terminals. Participants were defined as being at high risk of anxiety and/or depression according to the optimal cut‐off point of ≥11 on the Huaxi emotional‐distress index (HEI). Results: The rate of participants at high risk of anxiety and/or depression was 6.63%. Following participation in the BWBED‐SS + HSE, after controlling for demographics, type of hospital, and test time, the rates of participants considering themselves as having an emotional disorder and willing to seek mental health services among those at high risk of anxiety and/or depression increased from 29.93% to 47.45% (adjusted odds ratio [aOR] = 2.28, p = .002) and from 11.68% to 29.93% (aOR = 3.65, p < .001), respectively. Conclusions: The BWBED‐SS + HSE were associated with improved mental health awareness and service‐seeking attitudes among patients seeking nonpsychiatric clinical services in China.